A Community Built by Love and Death in Romeo and Juliet - Sun, Jiayu (Journal of Theory and Practice of Management Science, 2023)
Based on historical processes, Ferdinand Tönnies proposes that the two ways of human bonding are community and society, and suggests that community is based on emotional will from a psychological and volitional perspective, while society is allowed to exist based on rational calculation and choice of interests. As human history continues to evolve, human bonding is more based on interests. But human beings have always been full of expectations and aspirations for a community life of mutual help. The West has always had the expression “Endless Shakespeare”. Shakespeare’s plays are all-encompassing, but they also contain a rejection of extreme humanism. The spirit of fraternity that transcends class and even race, such as the abandonment of personal grudges, has something in common with the idea of “community”. Romeo and Juliet is not only about love, but also about love and death as a bridge to “community”. The century-long reconciliation between the Capulets and the Montagues embodies the Western desire for a better society— a “community”. Only by dissolving the gap between the “self” and the “other” and forming “a community with a shared future of mankind” based on the common responsibility of all human beings is the way out for the construction of the community.